Deployable lenticular stiffeners for origami-inspired mechanisms. Issue 5 (3rd September 2018) - Yellowhorse, Alden; Howell, Larry L.
ABSTRACT: Light-weight origami-inspired mechanisms can provide advantages in deployable space systems and other applications. However, a significant challenge in their design is ensuring that they are suﬃciently stiff. Compliant, deployable stiffeners utilizing a profile that approximates the Euler Spiral are proposed as one possible solution. It is shown that a structure with this specific profile, called a lenticular stiffener, permits stiffeners to be flattened using a force applied at their edge. Formulas for calculating the increase in stiffness are developed. Relations needed to design the deployment behavior of the stiffeners are also derived. Finally, advantages of different configurations of stiffeners are evaluated. These results are verified through simulation and experiments.